Chronic opioid use is associated with early biologic discontinuation in inflammatory bowel disease. Issue 6 (26th January 2021) - Rhudy, Christian; Perry, Courtney L.; Singleton, Michael; Talbert, Jeffery; Barrett, Terrence A.
Summary: Background: Chronic opioid use is associated with poorer clinical outcomes in inflammatory bowel disease. Aims: To investigate an association between chronic opioid use and persistence with biologic agents in management of inflammatory bowel disease. Methods: A total of 16 624 patients diagnosed with inflammatory bowel disease and receiving a first‐time biologic prescription from 2011 to 2016 were identified retrospectively from the Truven MarketScan Database. A cohort of 1768 patients were identified as chronic opioid users utilising outpatient prescription claims. Utilisation patterns of biologic therapies were assessed from inpatient administration and outpatient claims data, including persistence calculations. Information on healthcare utilisation and common comorbidities was also collected. A Cox regression model was constructed to assess the hazard of chronic opioid use on early discontinuation of biologic therapy controlling for disease severity. Results: A mean 1.5 different biologic agents were utilised by inflammatory bowel disease patients with chronic opioid use (vs 1.37 in the comparator group; P < 0.0001). A lower proportion of the chronic opioid use cohort persisted on biologic therapies to the end of the study period (16.2% vs 33.5% P < 0.0001). Inflammatory bowel disease patients with chronic opioid use utilised more healthcare resources and had a higher rate of comorbidities than the reference cohort. Patients with chronic opioid use were 23% more likely (hazard ratio 1.23; 95% CI [1.16‐1.31]) to be non‐persistent with biologic therapy while accounting for relevant markers of disease acuity. Conclusions: Chronic opioid use is associated with increased hazard of biologic discontinuation in inflammatory bowel disease. Symptoms of opioid withdrawal may mimic IBD flares thereby leading providers to inappropriately switch biologic therapies and compromise disease control. Abstract :